The readiness of educational professionals for sustainable development in education in Slovenia - Pangrčič, Polonca (Annales. Series historia et sociologia, 2022)
The purpose of the research was to focus on educators and their attitude towards international guidelines in education. A descriptive and causal non-experimental method was used. Using a representative sample (N = 525), we looked for correlations in the field of the holistic approach and the use of international guidelines. When searching for correlations between formal education and following the guidelines, 8 out of 10 correlations were statistically confirmed: imagination, creativity, memory, reasoning, respect for beauty, physical skills, communication/social skills and critical thinking, in favour of respondents with a lower level of education. Statistically significant correlations between knowledge of the holistic approach and adherence to the guidelines were not found.
Keywords: approccio olistico; celostni pristop; Commissione Europea; educational professionals; educatori; European Commission; Evropska komisija; holistic approach; logopedagogia; logopedagogika; logopedagogy; UNESCO; vzgojno-izobraževalni delavci